Prevalence of Primary Dysmenorrhea and Its Associated Risk Factors among Adolescent Girls in Selected Schools of Lusaka District, Zambia - Nachizya Edith Namukanga; Joseph Mumba Zulu; Margarate N Munakampe; Dennis M Ngosa; Samson Shumba; Choolwe Jacobs (Journal of Community Health Research)
Background: Dysmenorrhea is a common gynecological issue among young females. However, no studies in Zambia have examined the prevalence and associated factors of primary dysmenorrhea among adolescent girls. This study aimed to determine the prevalence and associated factors of primary dysmenorrhea among adolescents in selected schools in the Lusaka District. Methods: A cross-sectional study was conducted in eight randomly selected schools in Lusaka, including 400 post-menarche girls aged 10–19 years. Participants were selected via random sampling, and data were collected using a researcher-designed questionnaire informed by literature. The tool included closed-ended and Likert scale questions, piloted for reliability (Cronbach's alpha: 0.8–0.9). Analysis was performed using STATA version 14.2, with variables having p < 0.05 in multivariate logistic regression considered statistically significant. Results: All 400 participants responded (response rate: 100%). The prevalence of primary dysmenorrhea was 78% (312/400; 95% CI: 73.6%–82.0%). Major risk factors included a positive family history (p < 0.001) and symptoms like breast tenderness (p = 0.008), diarrhea (p < 0.001), headache (p = 0.002), and nausea (p = 0.015). Menstrual cycles lasting 31–35 days (p = 0.034) and moderate menstrual flow (p = 0.011) were also significant. Conclusion: Primary dysmenorrhea is highly prevalent among adolescents in Lusaka. Determinants included family history, long cycles, moderate flow intensity, and menstrual discomfort.